PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERMUATAN BUDAYA LOKAL DOMPU BERBASIS GAME - Mahdin; Lita Sasmita; Andi Prayudi; Nabila; Sisca Dwi Aprilia (Jurnal Muara Pendidikan, 2025)
This study aims to develop an Integrated Science and Social Studies (IPAS) Student Worksheet (LKPD) based on an RPG (Role-Playing Game) integrated with Dompu local culture through the Discovery Learning model in order to enhance elementary school students’ critical thinking skills. The research employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). The research subjects were 25 sixth-grade students of SDN 5 Woja in the 2025/2026 academic year. The instruments used included expert validation sheets, student response questionnaires, and post-test questions. The findings indicate that the developed product was categorized as highly valid, with an average expert validation score of 4.55. Student responses to the LKPD obtained an average score of 4.65 in the very good category, indicating that the media was able to improve students’ motivation and engagement in learning. The post-test results showed an average score of 81, categorized as good, which indicates an improvement in students’ critical thinking skills, particularly in identifying problems, analyzing information, and drawing logical conclusions. Therefore, the IPAS LKPD based on RPG with Dompu local culture is proven to be valid, practical, and effective for use in learning and can serve as an innovative alternative for integrating local cultural values into 21st-century learning.